Actinobacteria from avocado rhizosphere: antagonistic activity against Colletotrichum gloeosporioides and Xanthomonas sp.: Actinobacteria from avocado rhizosphere - Trinidad-Cruz, Jesús Rafael; Rincón-Enríquez, Gabriel; Evangelista-Martínez, Zahaed; Guízar-González, Cecilia; Enríquez-Vara, Jhony Navat; López-Pérez, Luis; Quiñones-Aguilar, Evangelina Esmeralda (REVISTA TERRA LATINOAMERICANA, 2021)
Actinobacteria from the rhizosphere of agricultural crops are a potential source of antagonists against phytopathogenic microorganisms. Thus, the objective of this study was to characterize the antagonistic activity in vitro of actinobacteria from the rhizosphere of avocado trees (Persea americana) against Colletotrichum gloeosporioides and Xanthomonas sp. Actinobacteria were isolated from rhizosphere soil samples of avocado trees var. Hass collected from an orchard from Ziracuaretiro, Michoacán. The isolated strains were assessed against C. gloeosporioides and Xanthomonas sp. by means of in vitro confrontation tests. The antagonistic activity was determined by measuring the radius and diameter of the growth inhibition zone of C. gloeosporioides and Xanthomonas sp., respectively. A total of 41 actinobacterial strains were isolated, of which 44% inhibited growth of at least one of the two plant pathogens. Specif ically, 15% of the isolates inhibited growth of C. gloeosporioides, 22% of Xanthomonas sp. and 7% of both phytopathogens. The mycelial growth inhibition radius of C. gloeosporioides fluctuated from 6.6 to 15.5 mm, while in Xanthomonas sp., the inhibition zone was from 15.5 to 62.7 mm. These results indicated the importance of rhizosphere actinobacteria as antagonists of phytopathogenic microorganisms, some of which could be used as potential biological control agents against anthracnose and bacterial leaf spot.